The Use of Instagram Stories at the Age of COVID-19 Pandemic - Syahnaz Savitri; Irwansyah Irwansyah (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
One of Instagram’s features, Instagram stories (IS), which allows users to access videos and photos for 24 hours, is one of the prevalent features used by Instagram users. This qualitative research aims to investigate the use of IS during the COVID-19 pandemic by referring to The Technology Acceptance Model (TAM) as a research framework. The framework observes ten external factors that influence the perception of ease of use and IS’s usefulness, affecting the user’s attitude to IS, leading to IS’s actual use. This study also found the pattern and form of IS uploads, as well as recommendations for the use of IS. Data were collected via interviews and observations of Informant’s Instagram Stories posts who are the active IS users who live in the red zones of COVID-19 spread in Indonesia. Overall, all Informants had good attitudes towards IS, which leads to the active use of IS.